Case Study of Concurrent Engineering in Stadium Construction - Kuna Segaran, Vrejenan; Kalaikumar, V.; Khamidi, M. Faris; Husna , Takaijudin (2010)
Application of concurrent engineering is widely adopted by industries especially civil engineering. Thus this case study discusses on the exercises of concurrent engineering in constructing a stadium, in particular the City of Manchester Stadium. Interviews were conducted to gather the information with three personnel whom are directly involved in the project. The study has revealed that appropriate usage of concurrent engineering have benefited the project specifically client in term of cost. An effective feasibility study was conducted involving designer, architect and contractors during design development stage. Collaboration among them resulted best design solution and minimized the design changes during the implementation stage. Apparently concurrent engineering could be adopted in for any kind of construction project as long the available expertise and experience are needed and most importantly willingness to take the challenge.